Broadband terahertz recognizing conformational characteristics of a significant neurotransmitter γ-aminobutyric acid. Issue 35 (28th June 2019) - Cheng, Chao; Zhu, Zhongjie; Li, Shaoping; Ren, Guanhua; Zhang, Jianbing; Cong, Haixia; Peng, Yan; Han, Jiaguang; Chang, Chao; Zhao, Hongwei
Abstract : γ-Aminobutyric acid (GABA) is the chief inhibitory neurotransmitter in the central nervous system, its conformational behavior is critical for selective biological functions and the process of signal transmission. Abstract : γ-Aminobutyric acid (GABA) is the chief inhibitory neurotransmitter in the central nervous system, its conformational behavior is critical for selective biological functions and the process of signal transmission. Although this neuroactive molecule has been extensively studied, its vibrational properties related to the conformation and intermolecular interactions in the terahertz (THz) band have not been identified experimentally yet. In this study, we applied a broadband THz time-domain spectroscopy (THz-TDS) system from 0.5 to 18 THz to characterize a unique THz fingerprint of GABA. The density functional theory calculation results agree well with the THz experimental spectrum. The study shows that the vibrational modes of GABA at 1.15 and 1.39 THz originate from distinct collective vibrations. The absorptions at the higher THz frequencies also carry part of collective vibrations, but more reflect the specific and local vibrational information, including the skeleton deformation and the rocking of the functional groups, which are closely associated with the conformation and flexibility of GABA. This study may help to understand the conformational transitions of neurotransmitter molecules and the resonant response to THz waves.